Climatic changes in India – (II) Temperature - PRAMANIK , S. K.; JAGANNATHAN, P. (MAUSAM, 1954)
Annual mean maximum and minimum temperature data of 30 meteorological stations distributed over India and Pakistan for which long and continuous records available are examined for (i) long terms trends (ii) short period oscillations and (iii) random or unsystematic components. The stations jon the west coast of India and the sub-Himalayan regions of month and northeast India have a tendency for increasing maximum temperature and those in the rest of the country extending in a northwesterly direction from north Madras coast to Baluchistan have a tendency for decreasing maximum temperature. In regards to minimum temperature except for a small strip extending from Orissa to the Vindhyas\, the c9ountry has a tendency for increasing minimum temperature.